Pycha króla jako problem teologiczny w Księdze Machabejskiej (1,3) - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2010)
Studies on IMacc 1,3a - a verse interesting on account of its historical context - lead to the conclusion that when remarking on the pride of the Macedonian King the author of the book uses the expression his heart was lifted, up not only as a reference to history, although history does confirm the king’s character. The quoted phrase has a highly theological connotation in the Bible and is used with reference to various characters who meet with an adequate response on the part of the God of Israel. The causes of human pride discussed in the article - success in life, riches and military victory - are by no means the only ones responsible for the increasing self-satisfaction felt by the characters. However, it seems that it is those causes of pride that most often threaten punishment to the willful.